A Review of Weather Forecasting Using Data Mining Techniques (International Journal of Engineering and Computer Science, 2018)
The vast dramatically changes occurs day by day in certain fields due to the development of advanced technology and nature one such among them is rainfall. The rainfall is the fragment of the agriculture and unable to understand the monsoon condition, predicating the crop yield and the soil fertility. Data mining is the techniques used to extract the knowledge from the set of data.This paper provides a survey of different data mining techniques being used in weather prediction or forecasting which helps the farmer for yield worthy productive and nourish the soil fertility such as artificial feed-forward neural networks (ANNs), fuzzy inference system, decision tree method, time series analysis, learning vector Quantization (LVQ) and biclustering technique.